Musafirtrip: Mobile application development for muslim travellers / Nur Awatif Ab Hamid - Ab Hamid, Nur Awatif (2021)
The emergence of Muslim travelers in the industry has become a global trend, with Muslim perception that Muslim travelers are preferred to travel has increased over time. The challenges for Muslim travelers when traveling to different countries nowadays have become a serious problem and quit worrying. The first problem is the number of food outlets with a halal certificate is difficult to identify. Secondly, difficult to find halal-friendly accommodation that offers based on Islamic rules when traveling. Therefore, this project aims to develop a mobile application for Muslim travelers to find halal food outlets and accommodation suitable for Muslims based on the user's location using a mobile phone as a platform. This project will be using the android platform. Besides, the objectives of the project are to identify the user requirements for MusafirTrip mobile application and interaction mainly, to design, and to develop MusafirTrip mobile application. The scope of this project is on area Shah Alam and the target user is Muslim travelers. The development of this application is using the Mobile Application Development Lifecycle (MADLC) methodology to complete this task. The research methodology contains seven phases. However, this project will be developing up until the testing phase only. The limitation and suggestions for future enhancement for this project are based on positive feedback from user testing results. In the future, this project is recommended to include a filtering function so that users can narrow down their search criteria and get more accurate results. The functions of the application are map navigation according to view the nearest halal accommodation and halal food outlets, and able to display the location. In a nutshell, the MusafirTrip mobile application has the potential to help Muslim travelers to find places when traveling